Filosofía e historia, ¿un diálogo de sordos? Puntos de contacto en los debates en torno a la experiencia histórica entre 1890 y 1960 - Rojas, Agustín (Historiografías, 2022)
This work examines, from a viewpoint of intellectual history, the particular links between historiography and philosophy prior to the “narrativist turn”. For this purpose, as much as pragmatic contexts of analysis are concerned, the foremost philosophical and historiographical debates, taken place between the 1890s and the 1960s, have been chosen, scenarios in which the epistemic matrices, shaping the so-called “historiographical operation”, are discussed. By identifying the main nuclear topics, it is possible to access the primitive foundations of the theory of history. In this way, the study of the debates makes it possible to exorcise the myths of singularity and illuminate the circulation of ideas, the mechanisms of reception, and the diversity of semantic fields. The objective of this article is to examine the scope and limits of Western historiographical projects in their tensions regarding philosophy. Without ignoring the philosophical poverty of historical science in its beginnings, unsuspected interstices can be highlighted through this search.